2006
DOI: 10.1002/asi.20513
|View full text |Cite
|
Sign up to set email alerts
|

Link decay in leading information science journals

Abstract: Web citations have become common in scholarly publications as the amount of online literature increases. Yet, such links are not persistent and many decay over time, causing accessibility problems for readers. The present study investigates the link decay phenomenon in three leading information science journals. Articles spanning a period of 7 years (1997-2003) were downloaded, and their links were extracted. From these, a measure of link decay, the half-life, was computed to be approximately 5 years, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
64
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 19 publications
11
64
2
4
Order By: Relevance
“…(Goh and Ng 2006) and categorized as uncheckable, rather than as an error. All percentages in the article from this point on refer to the searchable citations (100% = 2,650) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…(Goh and Ng 2006) and categorized as uncheckable, rather than as an error. All percentages in the article from this point on refer to the searchable citations (100% = 2,650) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…He concluded that during that time span, around 67% of the URLs -due to one reason or another -became inaccessible. Koehler's study was based on randomly selected websites, but inspired a range of subsequent investigations probing the extent of the problem within distinct research fields such as History [12], Information Science [13][14][15], Law [16][17] and Medicine [18][19][20]. Results vary according to the types of links investigated and the timespan of the study, but the conclusions are clear: Websites are updated at an increasing speed, and URLs are disturbingly unstable.…”
Section: Approachmentioning
confidence: 99%
“…The studies on web citation analysis in the past have witnessed the most frequent use of URLs (Casserly and Bird 2003;Spinellis 2003;Sellitto 2005;Maharana, Nayak, and Sahu 2006;Falagas, Karveli and Tritsaroli 2008;Goh and Ng 2007;and Moghaddam and Saberi 2011;Sampath Kumar and Manoj Kuma, 2012;Gul, Mahaj and Ali 2014). Studies focused on web resources have witnessed the loss of URLs.…”
Section: Vanished Urlsmentioning
confidence: 99%
“…The websites those are inherent in the web reinforces the scholarly communication. Many studies documented that use of Internet for scholarly information has become inevitable (Falagas, Karveli and Tritsaroli 2008;Goh and Ng 2007;Yang, Qiu and Xiong 2010).…”
Section: Introductionmentioning
confidence: 99%